Will Population Aging Attract Foreign Investment? -- An Empirical Study based on Provincial Panel Data in China - Lin, Jingru (Transactions on Economics, Business and Management Research, 2024)
Drawing on provincial panel data from China spanning 2005 to 2020, this paper investigates the impact of population aging on Foreign Direct Investment (FDI), integrating innovation levels and human capital within the analysis. Utilizing a two-way fixed effects model, a inverted U-shaped relationship between population aging and FDI inflows is identified, with spatial heterogeneity observed. Heterogeneity analysis across China's Eastern, Central, and Western regions shows that only the Eastern region demonstrates a pronounced inverted U-shaped relationship, emphasizing the role of regional economic development, industrial structures, and degrees of openness. Additionally, regional innovation levels and human capital exhibit significant positive effects on FDI, with the dynamic influenced by population aging also displaying an inverted U-shaped trend. Thus, policymakers should consider region-specific economic and demographic conditions to optimize FDI-related policies and leverage regional innovation capabilities and human capital to promote FDI inflows.